Diseño de una guía metodológica para implementar un sistema de gestión integrado QHSE para el área de mantenimiento de una empresa de transporte terrestre de hidrocarburos líquidos (2015)
This work suggested as a proposal for improvement to the maintenance area of TRANSPORTES LIQUIDOS DE COLOMBIA S.A. due to the growth in the volumes of land transportation of hydrocarbons it is necessary to implement the adequate controls for the optimization of the processes, allowing to comply with the guidelines of the integrated QHSE policy of the organization; which is why it became necessary to have a Methodological Guide for Integrated Management QHSE through the standards ISO 9001, ISO 14001 and OHSAS 18001, which allows optimizing their economic and human resources, increasing their productivity, ensuring compliance with legal requirements and its customers, through greater confidence, satisfaction and economic returns of the organization.